Versatile Role of Rab27a in Glioma: Effects on Release of Extracellular Vesicles, Cell Viability, and Tumor Progression - van Solinge, Thomas S.; Abels, Erik R.; van de Haar, Lieke L.; Hanlon, Killian S.; Maas, Sybren L. N.; Schnoor, Rosalie; de Vrij, Jeroen; Breakefield, Xandra O.; Broekman, Marike L. D. (Frontiers in Molecular Biosciences, 2020)
Introduction Glioma cells exert influence over the tumor-microenvironment in part through the release of extracellular vesicles (EVs), membrane-enclosed structures containing proteins, lipids and RNAs. In this study we evaluated the function of Rab27a in glioma and evaluated the feasibility of assessing its role in EV release in from glioma cells in vitro and in vivo. Methods Rab27a was knocked down via a short hairpin RNA (shRNA) stably expressed in mouse glioma cell line GL261, with a scrambled shRNA as control. EVs were isolated by ultra-centrifugation and quantified with Nanoparticle Tracking Analysis (NTA) and Tunable Resistive Pulse Sensing (TRPS). CellTiter-Glo viability assays and Cytokine arrays were used to evaluate impact of Rab27a knockdown. GL261.shRab27a cells and GL261.shControl were implanted into the left striatum of eight mice to assess tumor growth. Results Knockdown of Rab27a in GL261 glioma cells decreased the release of small EVs isolated at 100,000 x g in vitro (p=0.005), but not the release of larger EVs, isolated at 10,000 x g. GL261.shRab27a cells were less viable compared to the scramble control in vitro (p<0.005). A significant increase in CCL2 expression in shRab27a GL261 cells was also observed (p<0.001). However, in vivo there was no difference in tumor growth or overall survival between the two groups, while shRab27a tumors showed lower proliferation at the tumor borders. Decreased infiltration of IBA1 positive macrophages and microglia, but not FoxP3 positive Treg cells was observed. Conclusions Rab27a plays an important role in the release of small EVs from glioma cells, and also in their viability and expression of CCL2 in vitro. As interference in Rab27a expression influences glioma cell viability and expression profiles, future studies should be cautious in using the knockdown of Rab27a as a means of studying the role of small EVs in glioma growth. Still, the literature supports a vital role for glioma-derived EVs in tumor progression.